A diagnostic nomogram for delayed hemolytic transfusion reaction in sickle cell disease. Issue 12 (7th September 2016) - Mekontso Dessap, Armand; Pirenne, France; Razazi, Keyvan; Moutereau, Stéphane; Abid, Shariq; Brun‐Buisson, Christian; Maitre, Bernard; Michel, Marc; Galacteros, Frederic; Bartolucci, Pablo; Habibi, Anoosha
Abstract : Diagnosis of delayed hemolytic transfusion reactions (DHTR), one of the most dreaded complications of transfusion in patients with sickle cell disease (SCD), is challenging and not straightforward. Current diagnostic approaches are complex and not consensual; they are based on assessment of hemoglobin (Hb) drop and enhanced hemolysis, features also seen during classical vaso‐occlusive events. In this observational study, we tested the hypothesis that the rate of decline in HbA after an index transfusion is a surrogate marker for the destruction of transfused RBC, which could be used diagnostically. We examined 421 transfusion episodes (in 128 patients of a French referral center for SCD) for which an Hb electrophoresis was obtained within 1 week following an index transfusion and repeated within 2 months (before a subsequent scheduled transfusion or during an acute complication). Chart review found DHTR to be present in 26 cases (6.2%), absent in 389 cases (92.4%), and possible in six cases (1.4%). As expected, DHTR was associated with accelerated hemolysis (increased serum bilirubin and lactic dehydrogenase concentrations) and a decline in total Hb as compared to the early post‐transfusion value. However, the decline in HbA concentration appeared more effective in segregating between patients without DHTR and others. We propose a diagnostic nomogram for DHTR based on Hb A as a biologic marker of the survival of transfused RBCs. Am. J. Hematol. 91:1181–1184, 2016. © 2016 Wiley Periodicals, Inc.